Pengembangan Multimedia Interaktif Pengenalan Hewan Untuk Anak TK Berbasis Augmented Reality - Darmawan Aditama; Fardani Annisa Damastuti; Mohammad Robihul Mufid (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2022)
Abstract—The development of Information and Communication Technology (ICT) has changed the new face of education. The implementation of Information and Communication Technology (ICT) in educational institutions has become a must in educational institutions, not to close our eyes that schools are naturally responsive to technological developments. The use of interactive multimedia as a support for the teaching and learning process is considered to be able to increase flexibility in teaching and learning activities, especially for Kindergarten (TK) students. Children at this age should be introduced to the benefits of technology. So that in the future it is not wrong to use technology. An interactive multimedia application that makes it easy for students to learn anywhere and anytime using a mobile device. Learning abilities are focused on making animal recognition applications for kindergarten (TK) students. Because knowledge related to animals must be introduced to students from an early age. Interactive multimedia applications are made by utilizing mobile android and Augmented Reality which are packaged in the form of games (games).